Worte am Werk Wittgenstein über Sprache und Welt (Band 2) - Carrujo Covas, Luis Miguel (KIT Scientific Publishing, 2008)
The focus of this study on Wittgenstein's work is on the connection between language and world. Whereas this issue is of high relevance in the Tractatus, PU seems to unmask it as meaningless. It is widely assumed that the language-independent world has no place in the model of the linguistic-game. But is that true? In search of an answer the book provides a draft sketch of Wittgenstein's way of thinking which breaks with some current prejudice.